Kepemimpinan Kepala Madrasah Dalam Meningkatkan Kualitas Sarana Dan Prasarana Madrasah Aliyah Negeri di Provinsi Jambi - Firdaus Firdaus; Mukhtar Latif; Muhammad Taridi (Universitas Negeri Makassar, 2026)
The leadership of the madrasah principal is the most important factor in improving the quality of educational facilities and infrastructure, which play a crucial role in supporting the learning process in educational institutions. State Islamic Senior High Schools (MAN) in Jambi Province face various challenges in managing these facilities and infrastructure, including planning, procurement, utilization, and maintenance. This situation demands effective, visionary, and participatory leadership from the madrasah principal. This study, a preliminary study using a qualitative approach, aims to obtain an initial overview of the role of madrasah principal leadership in improving the quality of facilities and infrastructure at State Islamic Senior High Schools in Jambi Province, as well as to identify the supporting and inhibiting factors encountered. Data collection techniques were conducted through indirect observation, preliminary online interviews with madrasah principals and education staff, and documentation or literature studies related to the management of facilities and infrastructure in madrasahs. Data analysis in this preliminary study was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and drawing preliminary conclusions. The results of this pre-research identified several obstacles, including budget limitations, uneven quality of facilities across madrasahs, and a weak maintenance system. The findings of this pre-research are expected to form the basis for further, more in-depth research to formulate an effective madrasah principal leadership model to improve the quality of facilities and infrastructure at State Islamic Senior High Schools in Jambi Province. Keywords: Madrasah Principal Leadership, Facilities and Infrastructure Quality, Pre-Research